Efficient syntheses of bolaform surfactants from l-rhamnose and/or 3-(4-hydroxyphenyl)propionic acid1. Issue 6 (8th June 2015) - Obounou Akong, Firmin; Bouquillon, Sandrine
<x xml:space="preserve">Abstract</x> Efficient syntheses of symmetric and asymmetric bolaamphiphiles derived from l-rhamnose and/or 3-(4-hydroxyphenyl)propionic acid.